Green Defenders: A Review on Plant-Based Antioxidants Against Oxidative Injury (International Journal of Environmental Sciences, 2025)
Oxidative stress, resulting from an imbalance between endogenous antioxidant defences and reactive oxygen species (ROS), is a key driver of chronic disease onset and progression, such as cancer, cardiovascular disease, neurodegeneration, and metabolic syndromes. Plant antioxidants have become the focus of growing scientific and therapeutic attention over the past few decades because they have antioxidant properties such as scavenging ROS, chelation of pro-oxidant metals, and the modulation of redox-sensitive signalling. This review critically assesses the principal classes of plant antioxidants, flavonoids, phenolic acids, carotenoids, and alkaloids, their molecular mechanisms of action, pharmacological significance, and therapeutic potential.Despite promising preclinical data, clinical translation is obstructed by substantial hurdles like heterogeneity in extract composition, absence of standardised dosing and dose-response information, inferior bioavailability, and regulatory disparities. These factors constrain reproducibility, efficacy, and consumer confidence. To break these obstacles, the review calls for massive-scale, placebo-controlled clinical trials, standardisation of extract preparation, use of sophisticated delivery systems (e.g., nanoencapsulation), and incorporation of omics-based platforms to decipher complex biological interactions. The potential synergistic use with standard therapies and investigation of underutilised plant sources are also suggested as avenues for the future. By filling these gaps, plant antioxidants could become effective, multi-targeted drugs in the battle against oxidative damage and its related pathologies.